2019
DOI: 10.3390/cells8050462
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning in an Inflammatory Milieu Augments the Immunotherapeutic Function of Mesenchymal Stromal Cells

Abstract: Multipotent mesenchymal stromal cells (MSCs) have emerged as potent therapeutic agents for multiple indications. However, recent evidence indicates that MSC function is compromised in the physiological post-injury milieu. In this study, bone marrow (BM)- and adipose-derived (AD)-MSCs were preconditioned in hypoxia with or without inflammatory mediators to potentiate their immunotherapeutic function in preparation for in vivo delivery. Human MSCs were cultured for 48 h in either normoxia (21% O2) or hypoxia (2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 80 publications
0
29
0
8
Order By: Relevance
“…In one experimental setting, UCMSCs were stimulated with pro-inflammatory cytokines (hereafter referred to as 'primed') for 48 h when they reached 80% confluence. They were treated with an inflammatory cocktail containing 5 ng/mL TNF-α, 2.5n g/mL IFN-γ and 2.5 ng/mL IL-1β (Peprotech, London, UK) [11,14,15]. Figure 1 outlines the experimental plan and culture conditions of UCMSCs.…”
Section: Pro-inflammatory Priming Of Ucmscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one experimental setting, UCMSCs were stimulated with pro-inflammatory cytokines (hereafter referred to as 'primed') for 48 h when they reached 80% confluence. They were treated with an inflammatory cocktail containing 5 ng/mL TNF-α, 2.5n g/mL IFN-γ and 2.5 ng/mL IL-1β (Peprotech, London, UK) [11,14,15]. Figure 1 outlines the experimental plan and culture conditions of UCMSCs.…”
Section: Pro-inflammatory Priming Of Ucmscsmentioning
confidence: 99%
“…The MSCs secretome is variable, and the conditions MSCs are exposed to can change their functional properties [10]. For example, MSC-EVs from cells primed with pro-inflammatory cytokines (Tumor necrosis alpha (TNF-α), Interleukin 1 beta (IL-1β) and Interferon gamma (IFN-γ) have shown enhanced immunosuppressive properties against T-cells [11]. Likewise, MSC-EVs derived from cells grown in hypoxia (5% O 2 ) have also shown an enhanced ability to polarise M1 macrophages into M2 macrophages in mice compared to the MSC-EVs derived from normal oxygen conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Visceral ADSCs secrete higher quantities of inflammatory cytokines IL-6, IL-8, and TNF-α when compared to the subcutaneous ones [ 165 ]. ADSCs preconditioning with inflammatory or pro-inflammatory cytokines increase their survival and improved their responses to cancer and inflammation [ 32 , 153 , 165 , 166 , 167 ]. This epigenetically modification of the microenvironment of ADSCs might address cell ability to differentiate and migrate, and to restore cellular defects associated to aging.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ADSCs have been reported to regulate inflammation and participate in the phases of wound healing through their exosomes [ 10 , 24 , 25 , 26 , 27 , 28 , 29 ]. Within their microenvironment, ADSCs carried their immune-modulatory and regenerative effects through direct interaction with activated immune cells [ 30 , 31 , 32 ]. This cell network is the key regulator of skin regeneration and repair.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the concentration of inflammatory cytokines affects the immunomodulatory effects of MSCs on T cells (23)(24)(25). High concentrations of inflammatory factors can cause MSCs to exertan immunosuppressive effect, while insufficient levels of inflammatory factors can cause MSCs to play an immunological enhancement role (23).…”
Section: Introductionmentioning
confidence: 99%